Effect of fluoride on the thickness, surface roughness and corrosion resistance of titanium anodic oxide films formed in a phosphate buffer solution at different applied potentials (Research, Society and Development, 2020)
The anodizing process and anions type present in the electrolyte during anodic oxidation are important parameters to improve oxide biocompatibility. From these parameters, it is possible to control the thickness and surface roughness of the oxide film. This control is of major importance, once blood clots can be avoided when the oxide film on the metal substrate has a small surface roughness (Ra ≤ 50 nm). In this paper, the thickness, surface roughness, and corrosion resistance of the anodized titanium film were studied in a phosphate buffer solution containing fluoride anions (0.6 w.t % NaF), at 20 V, 40 V, 60 V, and 80 V, using atomic force microscopy (AFM), spectroscopic ellipsometry (SE), and electrochemical impedance spectroscopy (EIS) techniques. It was observed that thickness and roughness tend to increase as the applied potential rises. For oxides grown in the solution without NaF, the growth rate is roughly 1.3 ± 0.2 nm/V. Surface roughness generally presents the same behaviour. Moreover, EIS and SE thickness measurements agree at 20 V and 60 V but disagree at 80 V. This may be associated with a possible dielectric breakdown at 80 V. The oxide film formed at 60 V showed the best corrosion resistance in relation to the other studied potentials. Globular structures were also observed using AFM on surfaces at 40 V, 60 V, and 80 V, which suggests oxide film nucleation. Oxide films formed in solution with NaF presented lower thickness, excellent corrosion resistance, and low surface roughness (Ra ≤ 50 nm).